Current Profile of Adults Presenting for Preoperative Cochlear Implant Evaluation. (February 2018) - Holder, Jourdan T.; Reynolds, Susan M.; Sunderhaus, Linsey W.; Gifford, René H.
Considerable advancements in cochlear implant technology (e.g., electric acoustic stimulation) and assessment materials have yielded expanded criteria. Despite this, it is unclear whether individuals with better audiometric thresholds and speech understanding are being referred for cochlear implant workup and pursuing cochlear implantation. The purpose of this study was to characterize the mean auditory and demographic profile of adults presenting for preoperative cochlear implant workup. Data were collected prospectively for all adult preoperative workups at Vanderbilt from 2013 to 2015. Subjects included 287 adults (253 postlingually deafened) with a mean age of 62.3 years. Each individual was assessed using the minimum speech test battery, spectral modulation detection, subjective questionnaires, and cognitive screening. Mean consonant-nucleus-consonant word scores, AzBio sentence scores, and pure-tone averages for postlingually deafened adults were 10%, 13%, and 89 dB HL, respectively, for the ear to be implanted. Seventy-three individuals (25.4%) met labeled indications for Hybrid-L and 207 individuals (72.1%) had aidable hearing in the better hearing ear to be used in a bimodal hearing configuration. These results suggest that mean speech understanding evaluated at cochlear implant workup remains very low despite recent advancements. Greater awareness and insurance accessibility may be needed to make cochlear implant technology available to those who qualify for electric acoustic stimulation devices as well as individuals meeting conventional cochlear implant criteria.